Exploring angle-of-attack effects in the aero-acoustic response of a weapons bay at transonic and supersonic Mach number - Bacci, David; Saddington, Alistair J. (AIAA, 2022)
Numerical aero-acoustic analysis was conducted on a weapon bay model with doors, incorporating radar cross section reduction features. The effect of angle of attack on the aero-acoustic response of the cavity was analysed at a transonic Mach number of 0.85, and at a supersonic Mach number of 1.20. It was found that incidence had influence on both mean-flow features and acoustic response. Further, linear and angular accelerations induced by the flow on doors revealed potential adverse fluid-structure coupling when results were compared with modal analysis. Again, angle of attack did influence the aeroacoustic effects on the cavity door structure.
Keywords: Critical Angle of Attack; Freestream Mach Number; Modal Analysis; RADAR; Overall Sound Pressure Level; Supersonic Speed; Strouhal Numbers; Pressure Coefficient; Shear Layers; Fluid Structure Interaction